2011
DOI: 10.3892/etm.2011.294
|View full text |Cite
|
Sign up to set email alerts
|

DNA hypermethylation of the NOX5 gene in fetal ventricular septal defect

Abstract: Abstract. Ventricular septal defect (VSD) is the most comon form of congenital heart disease (CHD). DNA hypermethylation analysis may provide an insight into the molecular features and pathogenesis of this heart disease. Although aberrant DNA hypermethylation is implicated in the pathophysiology of this heart disease, only a limited number of genes are known to be epigenetically altered in VSD. We previously identified regulation of the NOX5 gene by hypermethylation in VSD fetuses by promoter methylation micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…ROS, derived by the NOX family, have roles in cell proliferation, transformation, differentiation, and apoptosis. NOX5 has been shown to be highly expressed during embryonic development, and hypermethylation of the NOX5 promoter region has been associated with congenital heart disease in human fetuses (39). Hypermethylation of NOX5 leads to transcriptional silencing (39) and a reduction in the production of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…ROS, derived by the NOX family, have roles in cell proliferation, transformation, differentiation, and apoptosis. NOX5 has been shown to be highly expressed during embryonic development, and hypermethylation of the NOX5 promoter region has been associated with congenital heart disease in human fetuses (39). Hypermethylation of NOX5 leads to transcriptional silencing (39) and a reduction in the production of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…NOX5 is the member of the NADPH oxidase family and is a basic source of reactive oxygen species (ROS). ROS have different roles, including transformation, apoptosis, proliferation and differentiation, and hypermethylation of NOX5 gene is associated with pregnancy disorders . Yeung et al also demonstrated hypermethylation of CpG sites of NOX5 in PE.…”
Section: Epigenetic Changes In Pementioning
confidence: 99%
“…Epigenetics may have a more profound role in the regulation of NOX5 expression in different cells types. The expression of NOX5 has been shown to be negatively influenced by DNA methylation 49 which may account for cell-specific regulation and changes in expression in disease states. The relatively ratio of different splice variants of NOX5 appears to vary with NOX5α(V1) the predominant form in blood vessels 41 , NOX5βand δ(V2 and V3) in endothelial cells 22 , NOX5α-γ(V1-V4) in smooth muscle cells 22 , NOX5β(V2) in podocytes 11 and NOX5ε(V6) in Barrett's esophageal adenocarcinoma cells 46 .…”
Section: Functional Significance Of Nox5mentioning
confidence: 99%